Subahnale dan Rang-rang Pembelajaran Matematika SMP - Junaidi Junaidi; Nourma Pramestie Wulandari; Deni Hamdani (Griya Journal of Mathematics Education and Application, 2021)
The purpose of this research is to find mathematical concepts in the cultural heritage of songket cloth and how to apply them as a medium for learning mathematics in junior high schools. The results of this study can be used as a reference for junior high school teachers to choose culture-based learning media related to student life, especially in Lombok. This research is an ethnomathematical research with the research method used is a qualitative research method with an ethnographic approach. The research was conducted in September, October, and November 2021 in Sukarara village, Lombok, West Nusa Tenggara. The subjects in this study were craft works in the form of songket cloth and songket weavers who were active in the village of Sukarara which consisted of three weavers. Data were collected by documentation, document observation, and interviews. The documents obtained were then analyzed related to the content of the mathematical concepts contained therein. The conclusion of this study is that the quality of mathematics learning can be improved by using the traditional songket subahnale cloth as a medium or learning aid. Some mathematical concepts that can be learned with songket subahnale as the medium are congruence, similarity, perimeter of flat shapes, area of flat shapes, folding symmetry, comparisons, pattern tracing. Songket fabrics that can be used as media are songket subahnale woven fabrics with geometric motifs such as diamond motifs, rang-rang motifs, and hexagons